Q: What is 3a x 2a x 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2a-5=-3a5a-5=05a=5a=0

2a2 x 3a-3 = (2 x 3)a(2 + -3) = 6a-1

Simplifying a = 3a + 12 Reorder the terms: a = 12 + 3a Solving a = 12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. a + -3a = 12 + 3a + -3a Combine like terms: a + -3a = -2a -2a = 12 + 3a + -3a Combine like terms: 3a + -3a = 0 -2a = 12 + 0 -2a = 12 Divide each side by '-2'. a = -6 Simplifying a = -6

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2

a + a + a - 2a = 3a - 2a = a

Related questions

2a2

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

3a x 2a =24

= 3 X 2 = 6 = a X a = a2 (a square) = 6a2 + 5 Answer

3a-2a = 1

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)

The problem 3a-1 and 2a-5 is greater by 7. This is a math problem.

2a-5=-3a5a-5=05a=5a=0

3a + (3b - 2a) + 5b =3a + 3b - 2a + 5b =(3a - 2a) + (3b + 5b) =a + 8b

3a + 2a = 5a

since a=1a, 3a-1a=2a

Simplifying a = 3a + 12 Reorder the terms: a = 12 + 3a Solving a = 12 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. a + -3a = 12 + 3a + -3a Combine like terms: a + -3a = -2a -2a = 12 + 3a + -3a Combine like terms: 3a + -3a = 0 -2a = 12 + 0 -2a = 12 Divide each side by '-2'. a = -6 Simplifying a = -6